Microstructure and Compressive Strength of Geopolymer Materials Based on Metakaolin with Hematite and Magnetite Gels as Additives - Dimace Lionel Vofo Ngnintedem; Jean Mermoz Siéwé; Hervé Kouamo Tchakouté; Claus Henning Rüscher (Sustainable Chemical Engineering, 2024)
The purpose of this work is to increase the compressive strength and improve the microstructure of geopolymer materials by adding hematite and magnetite gels, as well as their powders, cured at 80 °C. Hematite and magnetite were dissolved in 10 M sodium hydroxide. Dried gels of hematite and magnetite were then ground to produce powders of dissolved hematite and magnetite. For the production of various geopolymer materials, metakaolin was replaced by 0 and 10 wt.% of each additive and then mixed with the hardener, with the SiO2/Na2O molar ratio set at 1.6. The results show that the reference geopolymer has a compressive strength of 51.11 MPa. These values are 50.99 and 47.59 MPa for the geopolymer materials with 10 wt.% of dissolved magnetite gel and powdered dissolved magnetite cured at 80 °C, respectively. They are 59.52 and 63.23 MPa for those prepared using 10 wt.% of dissolved hematite gel and powdered dissolved hematite cured at 80 °C, respectively. Si, Al, Fe, Na,and Ti form a homogeneous phase in the geopolymer structures, with the exception of a few magnetite particles that are agglomerated in the geopolymer materials. Compressive strength was found to be improved by the use of hematite gel and dissolved hematite powder cured at 80 °C as additives. A slight reduction in compressive strength was observed when dissolved magnetite gel and powdered dissolved magnetite cured at 80 °C were used as additives.